1989
DOI: 10.1002/1097-0142(19890915)64:6<1290::aid-cncr2820640620>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of human T-cell leukemia virus type I infection in patients with hematologic and nonhematologic diseases in an adult T-cell leukemia-endemic area of Japan

Abstract: In order to clarify the prevalence of human T-cell leukemia virus type I (HTLV-I) infection in the Kagoshima district, Japan, a highly endemic area for HTLV-I, antibodies for HTLV-I (anti-HTLV-I) were examined in the sera of 6167 from healthy residents and patients with various hematologic and nonhematologic diseases. In healthy residents, including blood donors, the prevalence of anti-HTLV-I was 11.9% (562/4741 persons). The prevalence increased with age, and was significantly higher in in females than in mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

1991
1991
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 15 publications
0
21
0
1
Order By: Relevance
“…Outside Africa, Hanada et al (1989) documented HTLV-1 coinfection in 25.8% of 525 LPs living in a highly endemic area in Japan for HTLV-1 whereas the seroprevalence of HTLV-1 in healthy controls was 11.9%. Hideroni et al (1998) showed that leprosy subjects from two sanatoria in Japan had a higher HTLV-1 prevalence than the general Japanese population from the same regions.…”
mentioning
confidence: 99%
“…Outside Africa, Hanada et al (1989) documented HTLV-1 coinfection in 25.8% of 525 LPs living in a highly endemic area in Japan for HTLV-1 whereas the seroprevalence of HTLV-1 in healthy controls was 11.9%. Hideroni et al (1998) showed that leprosy subjects from two sanatoria in Japan had a higher HTLV-1 prevalence than the general Japanese population from the same regions.…”
mentioning
confidence: 99%
“…Strongyloidiasis, tuberculosis, and leprosy are well-recognized infection complications of chronic HTLV-1 infection (HTLV-1 carriers); 19 they are associated with the immunodeficiency caused by chronic HTLV-1 infection. 20 On the other hand, to our best knowledge, the present report is the first report of cryptococcal lymphadenitis in an HTLV-1 carrier.…”
Section: Discussionmentioning
confidence: 46%
“…The association of leprosy and HTLV-1 infection has been observed in Japan and África 7,8 . Decreased survival among coinfected individuals was previously observed, without correlation with the clinical subtype of leprosy, which was attributed to other infectious diseases 9 .…”
Section: References Discussion Financial Supportmentioning
confidence: 93%